AGE, BODY MASS INDEX AND SEVERITY OF PRIMARY CHRONIC VENOUS DISEASE - Musil, Dalibor; Kaletova, Marketa; Herman, Jiri (Biomedical papers, 2011)
Aim: The aim of this cross-sectional prospective study was investigate whether there is a correlation between age, BMI and severity of chronic venous disease (CVD), evaluated clinically (CEAP classification) and anatomically (extent of the epifascial venous reflux).Methods: 213 patients, 65 males (30.5%, mean age 45.1±13.9 years) and 148 females (69.5%, mean age 47.5±13.5 years) were divided into three age categories: 18-40 years (40.8%), 41-74 years (56.3%) and ≥75years (2.8%). BMI was classified as normal weight (18.5 -
Keywords: Chronic venous disease/Risk factors/Age/Body Mass Index